1) 8 + 4 = -5 + 7
12 = 2
FALSE
2) y = -11x + 4
(0, -7): -7 = -11(0) + 4 ⇒ -7 = 0 + 4 ⇒ -7 = 4 False
(-1, -7): -7 = -11(-1) + 4 ⇒ -7 = 11 + 4 ⇒ -7 = 15 False
(1, -7): -7 = -11(1) + 4 ⇒ -7 = -11 + 4 ⇒ -7 = -7 True
(2, 26): 26 = -11(2) + 4 ⇒ 26 = -22 + 4 ⇒ 26 = -18 False
Answer: C
3) Input Output
0 0
1 3
2 6
3 9
4 12
5 15
6 18
Rule: input is being added by 1, output is 3 times x
4) c = 65h
5) 2x = -6
![(2x)/(2) = (-6)/(2)](https://img.qammunity.org/2019/formulas/mathematics/high-school/3p1pf2hvus9u61h4wh92j3288yz1jeql90.png)
x = -3
6) 8j - 5 + j = 67
9j - 5 = 67 added like terms (8j + j)
+5 +5
9j = 72
![(9j)/(9) = (72)/(9)](https://img.qammunity.org/2019/formulas/mathematics/high-school/jhh39mnrx1i1sn02ymndr7ghptvqrvm8za.png)
j = 8
7) y = mx + b
-b -b
y - b = mx
![(y - b)/(x) = (mx)/(x)](https://img.qammunity.org/2019/formulas/mathematics/high-school/olqv0vi41iqu4rti8zrhon88mmzs0zcec2.png)
![(y - b)/(x) = m](https://img.qammunity.org/2019/formulas/mathematics/high-school/9jzwo2ca3panm7otj7tjt5h149hns3qc39.png)